2010
DOI: 10.5047/eps.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of large-scale variations in convective available potential energy (CAPE) and solar cycle over temperature in the tropopause region at Delhi (28.3°N, 77.1°E), Kolkata (22.3°N, 88.2°E), Cochin (10°N, 77°E), and Trivandrum (8.5°N, 77.0°E) using radiosonde during 1980–2005

Abstract: We have shown the relationship between seasonal, annual, and large-scale variations in convective available potential energy (CAPE) and the solar cycle in terms of temperature at the 100-hPa pressure level using daily radiosonde data for the period 1980 • N, 77. • E) and Trivandrum (8.5• N, 77.0 • E), India. In general, there was a tendency for increases in CAPE to be associated with decreases in temperature at the 100-hPa pressure level on all time scales. Decreasing linear trends in temperature were found at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Surface temperature does not show any role on convective rain in R 1 region, although positive role is observed in R 2 region. Present results are consistent with that of Dhaka et al (2010) who showed that high CAPE is associated with high rainfall and that of Roy Bhowmik et al (2008) who reported high value of CAPE during the pre-monsoon period.…”
Section: Lightning Convective Rainfall and Meteorological Parametersupporting
confidence: 96%
“…Surface temperature does not show any role on convective rain in R 1 region, although positive role is observed in R 2 region. Present results are consistent with that of Dhaka et al (2010) who showed that high CAPE is associated with high rainfall and that of Roy Bhowmik et al (2008) who reported high value of CAPE during the pre-monsoon period.…”
Section: Lightning Convective Rainfall and Meteorological Parametersupporting
confidence: 96%
“…Hence, to find out the periodicities in the average long-term trends, the time series of all regions are averaged and then subjected to the EMD technique, which reveals the existence of four main periodicities, namely 1.5-2.5 years, corresponding to the QBO, 4-6 years, corresponding to ENSO, 10-12 years, corresponding to the solar cycle, and 16-20 years. A similar multi-decadal climatic oscillation was also reported by Dhaka et al (2010). Hence for simplicity, this periodicity has been renamed as the Multi-decadal Climatic Oscillation (MCO).…”
Section: Effect Of Specific Periodicities On Long-term Trendssupporting
confidence: 69%
“…found to strongly influence the convective strengths over the Indian region (Manohar et al, 1999;Dhaka et al, 2010).…”
Section: Dataset and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Arakawa and Schubert, 1974;Moncrieff and Miller, 1976;Washington and Parkinson, 2005). Many of the cumulus parameterization schemes make use of CAPE in constructing closures (Donner and Phillips, 2003). The diurnal variation of CAPE is of primary importance for understanding the sensitivity of convection schemes in the model for producing the diurnal cycle of precipitation (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%